Jurnalisme Dakwah di Media Online (Framing Rubrik Feature Hidayatullah.com) - Eko Wahyudi; Dina Nakita; Septyan Dwi Nuryanto (Kalijaga Journal of Communication, 2021)
As for those who are one of the "signs" that Islamic da'wah must be able to blend in with the presence of sites or news sites or news portals carrying Islamic values. The emergence of news portals that focus on the issue and point of view of Islam, becoming a trigger for introducing Islam to all corners of the world. However, the problem in this era is also whether it is properly wrapped in Islam in the internet and whether it can be said to do da'wah messages. These questions do not seem to be easily answered and concluded because there are quite a lot of online media that calls Islam, especially in Indonesia. Therefore, researchers here take one online media that has been established for a long time, namely Hidayatullah.com. It is known that the media can be said to be consistent in providing an Islamic point of view. The researcher analyzed one of the rubrics in the media, namely on the Feature Rubric in the March 2021 edition The citipulation provides an affirmation that even though the content contains coverage, can still be inserted by verses. As for those who researchers, but it is Hidayatullah.com taking a resource person who is able to motivate in increasing faith. The issues raised are also quite selective as they can provide insight into Islamic values and increase their readers' faith.